Temperate Blind Signature Scheme for Particular Subspaces - Oana-Adriana Ticleanu; Ioan Daniel Hunyadi; Nicolae Constantinescu (Applied Sciences, 2025)
The development of information security mechanisms follows a cyclic refinement model: new cryptographic solutions are proposed, their limitations are studied, and improvements are introduced to overcome those limitations. This paper contributes to this process by proposing a blind signature scheme with tunable anonymity, adapted to application-specific requirements. The core of the model is a parameter T that allows the user to balance confidentiality with transparency from the settings and adapt the signature behavior to the particular requirements of a beneficiary. Compared to the models currently used in blind signature protocols, this approach offers improved resistance to brute force attacks and improves security against adaptive and man-in-the-middle threats. Due to the reduced computational power requirements needed to calculate cryptographic primitives, it is usable for devices with power constraints. Being able to be integrated into a blockchain infrastructure, the process supports both persistent and verifiable data records, which gives it flexibility to adapt to different types of decentralized platforms.